Cholecystoduodenostomy for Treatment of Biliary Obstruction Secondary to Feline Platinossomosis - Teixeira Amado Jorge, Ana Luiza; Mendes de Freitas, Dilma; Coelho Borges, Franciele Júlia; Santos Lacerda, Moacir; Piva Maria, Bruna; Scarpin de Sá, Simone; Rodrigues Rosado, Isabel; Gabellini Leonel Alves, Endrigo (Acta Scientiae Veterinariae, 2020)
Background: Platynosomum spp. it is a trematode that has a predilection for the liver and biliary tissues whose infection is acquired through the ingestion of metacercarian gecko viscera. Felines are the definitive hosts and clinical signs are variable. The diagnosis is through history, hematological and biochemical exams, ultrasound, bile cytology or histopathology. The treatment of choice is cholecystoduodenostomy. This paper aims to report the case of a cat who was treated at the Uberaba Veterinary Hospital with chronic cholangitis secondary to platinosomosis, but there was a transfusion reaction and she died. Case: A 4-year-old, uncastrated SRD cat was treated at the Uberaba Veterinary Hospital complaining of severe episodes of vomiting three days ago, hyporexia and darkened urine. The general clinical examination showed moderate dehydration, jaundice and hepatomegaly. The animal was hospitalized for better investigation of its condition. Increased values of ALT, alkaline phosphatase and all bilirubins were observed. Ultrasound showed liver suggestive of liver disease and steatosis, and gallbladder without alteration. During hospitalization, she remained jaundiced and hypoxic, and the esophageal tube was placed. The initial clinical suspicion was cholangiohepatitis. Liver biopsy and cholecystoduodenostomy were then suggested, with refusal by the tutor. The ultrasound was repeated and showed the same alterations described, besides cholangitis. Stool examination was negative for Platynosomum spp. and positive for Isospora spp. The patient was treated with anthelmintic for three days and received supportive treatment for another week until the tutor authorized cholecystoduodenostomy. During surgery, cholecystocentesis was performed and the parasite Platynosomum spp. in adult form. After four days, a new blood count was done and the animal was still anemic and the blood transfusion was chosen. The patient died within moments of the transfusion procedure. Discussion: Platynosomum spp. it is a trematode whose ultimate host is the domestic felines and inhabits liver, gallbladder and bile ducts causing biliary obstruction and even fibrosis. In the present report, the tutor reports that the cat had several episodes of vomiting and reduced appetite. Feline jaundice is normal in cases where cholestasis causes a two to three-fold increase in bilirubinemia from normal values. The increase was verified in the analyzed feline. Physical examination revealed jaundice and abdominal palpation suggestive of hepatomegaly. Ultrasound suggested cholangiohepatitis. Without improvement, liver biopsy and cholecystoduodenostomy were suggested, with tutor refusal. After repeated ultrasound, the images suggested cholangitis and the stool examination was negative for Platynosomum spp. The definitive diagnosis for this disease is through liver biopsy, visualization of the operated eggs or the adult form of the parasite in feces or bile as suggested in this case. However, in cases where there is total obstruction of the bile ducts, the eggs are not eliminated in the digestive system and the examination may be false negative as in this case. After the exams, the cat was submitted to cholecystoduodenostomy surgery where gallbladder puncture was performed for microscopic evaluation, and the parasite Platynosomum spp. in adult form. Most cats have blood type A, but even when the donor has the same blood type, cross-reaction may occur, so compatibility testing should be performed prior to any transfusion, thus reducing the risk of transfusion reactions. The patient died within moments of the transfusion procedure.